Statement of Peer Review - Teen-Hang Meen; Hsi-Hsien Yang; Cheng-Fu Yang (Engineering Proceedings, 2025)
In submitting conference proceedings of the 2024 IEEE 6th International Conference on Architecture, Construction, Environment and Hydraulics (IEEE ICACEH 2024) to Engineering Proceedings, the volume editors of the proceedings certify to the publisher that all papers published in this volume have been subjected to peer review administered by the volume editors [...]